General Well-Being in Workers: Determinant Analysis, Literature Development, and Research Gap through Systematic Literature Review - Yusuf Radityawan Idrad; Aulia Shafira Vanessa; Silvia Tri Handayani (International Journal Labs, 2026)
The increasing complexity of the modern work environment has made worker wellbeing a strategic issue for organizational sustainability. Changes in workplace systems, digital transformation, flexible working arrangements, and rising psychosocial risks have expanded the understanding of wellbeing beyond physical health into a multidimensional concept involving psychological, social, organizational, occupational, and technological aspects. This study aims to analyze the development of research on general wellbeing among workers, identify the main determinants influencing worker wellbeing, and map existing research gaps and future research directions. This study employs a Systematic Literature Review (SLR) approach using scientific articles indexed in the Scopus database. The literature selection process follows the PRISMA framework, resulting in 58 eligible international articles published between 2021 and 2026. The findings indicate that research on worker wellbeing has increased significantly, particularly in recent years, with major determinants categorized into six dimensions: individual psychological factors, organizational factors, social factors, job characteristics and demands, physical health and occupational safety, and technology-related factors. The synthesis also reveals that previous studies remain fragmented, focusing mainly on specific wellbeing dimensions and occupational groups rather than integrating wellbeing as a comprehensive construct. This study concludes that general wellbeing among workers is a multidimensional phenomenon requiring a holistic approach. The findings contribute theoretically by strengthening wellbeing frameworks and practically by supporting organizations in developing comprehensive worker wellbeing strategies.